2021
DOI: 10.1002/aenm.202102515
|View full text |Cite
|
Sign up to set email alerts
|

A Novel In Situ High‐Temperature Magnetometry Method for Radiofrequency Heating Applications

Abstract: reactor and heat transfer into a single step. Moving toward renewable electricity as the source of heat for chemical reactions will enable the decarbonization of the chemical process industries as around 60% of process heating at present comes from fossil fuels. [3] Direct RF heating elevates the catalyst temperature above the bulk reactor temperature. This reduces the impact of noncatalytic hot-spots and has been shown to enhance yields for a variety of organic synthesis and pyrolysis reactions. [4][5][6] Low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The heating power of ferri-magnetic maghemite powder was measured by reflected impedanceometry up to 175 °C using a bespoke work coil and heating arrangement (figure 2, refer to SI for experimental details). The synthesis and characterization of the maghemite powder is described in a previous work [7].…”
Section: Evaluation Of Reflected Impedance For Magnetic Hysteresismentioning
confidence: 99%
See 2 more Smart Citations
“…The heating power of ferri-magnetic maghemite powder was measured by reflected impedanceometry up to 175 °C using a bespoke work coil and heating arrangement (figure 2, refer to SI for experimental details). The synthesis and characterization of the maghemite powder is described in a previous work [7].…”
Section: Evaluation Of Reflected Impedance For Magnetic Hysteresismentioning
confidence: 99%
“…Data was simultaneously collected using the 3-coil pick-up coil magnetometry technique which has been described in a previous work [7] and compared to the reflected impedance results. Due to the intensity of heat transfer into the susceptor material, the temperature rise within the susceptor can exceed the response lag time of a thermocouple measuring the bed temperature.…”
Section: Evaluation Of Reflected Impedance For Magnetic Hysteresismentioning
confidence: 99%
See 1 more Smart Citation
“…It may not be possible to fully saturate a magnetic material depending on the equipment available, and Noble et al demonstrated that minor hysteresis loops for an induction heated sample may be measured in-situ using pickup coil magnetometry. A simplified model of magnetisation is required for inferring a magnetic sample temperature in realtime due to the rapid heating rates of induction heating of magnetic samples [6] and the need to use low cost, reliable digital signal processing to replicate this technique in the industrial setting of a chemical synthesis process. There are a number of criteria that a model of magnetic hysteresis must satisfy to be practically applied to induction heating hysteresis loops.…”
Section: Introductionmentioning
confidence: 99%
“…Noble et al [6] established a semi-theoretical arctangent model that successfully models the magnetic hysteresis heating power at applied field strengths well below saturation. This model will be referred to as the LineArc model due to the presence of both linear and arctangent terms.…”
Section: Introductionmentioning
confidence: 99%